2018
DOI: 10.11609/jott.3850.10.9.12163-12172
|View full text |Cite
|
Sign up to set email alerts
|

<b>Foraging and roosting ecology of the Lesser Dog-faced Fruit Bat <I>Cynopterus brachyotis</I> (Mammalia: Chiroptera: Pteropodidae) in southern India</b>

Abstract: The Lesser Dog-faced Fruit Bat Cynopterus brachyotis was found at higher elevations but since there is a paucity of reports on its distribution and habitat selection, an inventory was made at four locations in the Eastern and Western Ghats of southern India where the elevation ranged from 200–1,500 m.  The C. brachyotis roosts were distributed between 600–1,500 m.  Day roosts were found at an elevation of about 1,000m in Sirumalai and Yercaud Hill stations.  Mist-netting studies, however, revealed that C. brac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…3k). According to Mapatuna et al (2002), this species was only found in forest habitats in Sri Lanka, but our results indicate that C. brachyotis also flies over agricultural habitats, which is in agreement with Tan et al (1998) and Karuppudurai & Sripathi (2018). We found that pteropodid bats use tea plantations to find foods growing in shade trees as well as for moving between forest patches.…”
Section: Notes On the Family Pteropodidaesupporting
confidence: 85%
“…3k). According to Mapatuna et al (2002), this species was only found in forest habitats in Sri Lanka, but our results indicate that C. brachyotis also flies over agricultural habitats, which is in agreement with Tan et al (1998) and Karuppudurai & Sripathi (2018). We found that pteropodid bats use tea plantations to find foods growing in shade trees as well as for moving between forest patches.…”
Section: Notes On the Family Pteropodidaesupporting
confidence: 85%
“…C. brachyotis is the biggest contributor of species captured for the family Pteropodidae. Members of C. brachyotis can be found in many habitats including primary forest, secondary forest, agricultural landscape, orchard, mangrove, hill, and disturbed habitats (Ketol et al, 2009;Struebig et al, 2010;Karuppudurai et al, 2018). The family Hipposideridae is a diverse group of insectivorous bats (Murray et al, 2018).…”
Section: Species Accountsmentioning
confidence: 99%